2019
DOI: 10.1177/0967391119856140
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric studies and AC conductivity of piezoelectric barium titanate ceramic polymer composites

Abstract: In this work, ceramics barium titanate (BT) polymer composites were prepared with BT/polyvinyl alcohol (PVA) having a ceramic concentration of 10, 30, and 50% by weight using solution casting method. The prepared thin film samples were characterized by X-ray diffraction for phase analysis. Scanning electron microscope (SEM) studies on composite films revealed ceramic crystallites are well dispersed in the polymer matrix. The dielectric constant ( εr) and the AC conductivity at room temperature and at different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 20 publications
6
11
0
Order By: Relevance
“…On the other hand, the low signal from high frequencies is connected with the linear increase of conductivity and attributed to the loss of energy due to polarization of chemical dipoles. Similar dielectric behavior was reported for other polymers filled with BT ceramic material (Yao et al, 2018;Ahmed et al, 2018;Beena & Jayanna, 2019). However, at 1 kHz and 2% BT in HPC, the prepared composites have slightly smaller values for ε' and ε'' than those found in literature for PVA/BT (Beena & Jayanna, 2019), polypyrrole/BT (Ahmed et al, 2018), while the permittivity of our samples is higher than that reported for polypropylene/BT (Yao et al, 2018) and PEO/CMC/BT (Morsi et al, 2019).…”
Section: Dielectric Constant and Electric Energy Densitysupporting
confidence: 85%
“…On the other hand, the low signal from high frequencies is connected with the linear increase of conductivity and attributed to the loss of energy due to polarization of chemical dipoles. Similar dielectric behavior was reported for other polymers filled with BT ceramic material (Yao et al, 2018;Ahmed et al, 2018;Beena & Jayanna, 2019). However, at 1 kHz and 2% BT in HPC, the prepared composites have slightly smaller values for ε' and ε'' than those found in literature for PVA/BT (Beena & Jayanna, 2019), polypyrrole/BT (Ahmed et al, 2018), while the permittivity of our samples is higher than that reported for polypropylene/BT (Yao et al, 2018) and PEO/CMC/BT (Morsi et al, 2019).…”
Section: Dielectric Constant and Electric Energy Densitysupporting
confidence: 85%
“…Inset graph shows variation of real part of permittivity at 1 kHz with BT loading On the other hand, the low signal from high frequencies is connected with the linear increase of conductivity and attributed to the loss of energy due to polarization of chemical dipoles. Similar dielectric behavior was reported for other polymers filled with BT ceramic material (Yao et al, 2018;Ahmed et al, 2018;Beena & Jayanna, 2019). However, at 1 kHz and 2% BT in HPC, the prepared composites have slightly smaller values for ε' and ε'' than those found in literature for PVA/BT (Beena & Jayanna, 2019), polypyrrole/BT (Ahmed et al, 2018), while the permittivity of our samples is higher than that reported for polypropylene/BT (Yao et al, 2018) and PEO/CMC/BT (Morsi et al, 2019).…”
Section: Figure 10supporting
confidence: 85%
“…Also, when the filler concentration increases, the interparticle distances are reduced, leading to the more stressed regions, 17,19,20 and it is observed from the zoomed inset in Figure 2(a) that the particle distances were even less than the size of the nanofiller when increased in the filler concentration. The particle agglomeration results differently, and this has also been reported by Paul and Sindhu 19 in the early experimental studies and Beena and Jayanna 21 for the dielectric studies on piezoelectric BaTiO 3 ceramic polymer composites.…”
Section: Resultssupporting
confidence: 64%